Mapping the Malaria Receptivity Area in Biak Regency, Papua Province - Trivano Yonathan Lenakoly; Zusana Lena Tulak (Miracle Journal of Public Health, 2022)
Malaria is an infectious disease caused by the protozoan parasite of the genus Plasmodium. This disease is transmitted through the bite of the Anopheles mosquito. Malaria is found in almost all parts of the world,According to data from the Ministry of Health, the incidence of malaria in Papua is 64,030 per 1,000 population. The purpose of this study was to determine the malaria receptive area in Biak Regency. The working area of the Bosnik Health Center and the Marauw Health Center. The material used in this study is the Larvae Entomology Survey Kit, the method used in this study is the Observational Survey of Anopheles Sp. The results of this study were from 8 breeding place points conducted by a larval survey, 2 positive points of Anopheles Sp larvae were found which were located in 2 villages, namely Orwer Village and Marauw Saba Village, Biak Regency, Papua Province. Anopheles Sp larvae were still found in Orwer and Saba villages and were included in the Malaria Receptive Area Category.It is necessary to prevent and control malaria vectors in the work area of the Biak Numfor District Health Office, both physically (pond stockpiling/sanitation engineering), chemical (insecticide and larvicide administration) and biologically (sowing fish as natural predators of Anopheles Sp larvae).